Fabrication of three-dimensional hybrid nanostructure-embedded ITO and its application as a transparent electrode for high-efficiency solution processable organic photovoltaic devices. Issue 9 (9th February 2017) - Kim, Jeong Won; Jeon, Hwan-Jin; Lee, Chang-Lyoul; Ahn, Chi Won
Abstract : Well-aligned, high-resolution (10 nm), three-dimensional (3D) hybrid nanostructures consisting of patterned cylinders and Au islands were fabricated on ITO substrates using an ion bombardment process and a tilted deposition process. Abstract : Well-aligned, high-resolution (10 nm), three-dimensional (3D) hybrid nanostructures consisting of patterned cylinders and Au islands were fabricated on ITO substrates using an ion bombardment process and a tilted deposition process. The fabricated 3D hybrid nanostructure-embedded ITO maintained its excellent electrical and optical properties after applying a surface-structuring process. The solution processable organic photovoltaic device (SP-OPV) employing a 3D hybrid nanostructure-embedded ITO as the anode displayed a 10% enhancement in the photovoltaic performance compared to the photovoltaic device prepared using a flat ITO electrode, due to the improved charge collection (extraction and transport) efficiency as well as light absorbance by the photo-active layer.